Radio frequency (Rf) front-end design of radio access point for radio over fiber (Rof) technology - Ngah, Razali (Faculty of Electrical Engineering, 2008)
Wireless network based on radio over fiber (RoF) technology has been proposed as a promising cost effective solution to meet ever increasing user bandwidth and wireless demands. In this network, a central station (CS) is connected to numerous functionally simple radio access point (RAP) via an optical fiber. The aim of this project is to design a radio frequency (RF) front end of RAP for downlink transmission (CS to RAP). The RF front end consists of bandpass filter (BPF) and power amplifier (PA) which operating at 2.4 GHz band. The only components required at the passive RAP are electro absorption modulator (EAM) and antenna where EAM is used as a remote transceiver. There are practical limitations on the power that can produce by the passive RAP which can affect the dynamic range. In order to improve the dynamic range of passive picocell (RAP), the PA is placed between the EAM and the antenna. Picocells use power lower than 1 Watt (30 dBm). BPF is needed to remove out undesired frequency from nonlinear effect of fiber and pass through the signal at the operating frequency. The implementation of design is based on microstrip technology and Advanced Design System (ADS) software from Agilent is used to perform the simulation of front end design. In the simulation, the analyses of scattering parameters are concerned which presents the gain and return loss of the front end. At the end of design, the combination between parallel couple BPF and PA is purposed as a RF front end of RAP for RoF technology.